PENERAPAN METODE LATIHAN TERBIMBING DALAM UPAYA MENINGKATKAN KETERAMPILAN SISWA KELAS I JURUSAN MESIN PRODUKSI - Muhsin, Yahya; Paramata, Dewi Diana (Jurnal Entropi, 2009)
This research aim to improve skill to use the measuring instrument of shove and micro meter of student in Majors of Technical Engineering Produce of the SMK 3 Gorontalo through guided practice method. This research expected useful can grow enthusiastic of student to learn the physics items, developing ability and professionalism to face and solve the problem of process of physics study. This type of Research is class action research which used the descriptive method. The Result of research indicated that the guided practice method can improve the skill of the student in using measuring instrument. The improvement of skill of student above, meaning that hypothesis of action which have been formulated, which is: If in study use the guided practice method, hence skill to use the measuring instrument shove and micro meter of student in class of Majors Technical Engineering Produce in the SMK 3 Gorontalo improve is acceptable. So conclude that use of guided practice method will improve the skill to use of the measuring instrument shove and micrometer of student in class of Majors Technical Engineering Produce in the SMK 3 Gorontalo.